Primordialisme dan Perilaku Memilih Etnis Melayu pada Pemilihan Gubernur Kepulauan Riau 2005-2015: Primordialism and Voting Behavior of Malay Ethnic during the 2005-2015 Riau Islands Governor Election - Kustiawan Kustiawan; Rumzi Samin (Society, 2020)
This research aims to examine primordialism and voting behavior of Malay ethnic during the 2005-2015 Riau Islands governor election (Pemilihan Gubernur or Pilgub). The political phenomenon in Riau Islands seems to be different from other areas where other Malays dominate since non-Malay ethnic candidates won the governor election. This research used a qualitative method with a descriptive technique. The data were collected using in-depth interviews and direct observation. Informants were selected using a purposive sampling technique. The result found that people of Malay ethnic are open-minded. The candidates elected also can prove qualified personal and successfully leading the Malay ethnic people in moving ahead. Non-Malay ethnic won the Riau Islands (known as Kepri (Kepulauan Riau)) governor election determined by 1) The political identity of Malay ethnic people is open-minded, coexisting Islamic identity, speaking Malay language, practicing Malay culture, and committing to build and develop Malay ethnic people, so the candidates identified as part of Malay ethnic people and considered by the Malay ethnic people as a candidate for leader of the Malay people in a broadening sense; 2) the figure of candidates can socialize with people of Malay ethnic; 3) other minority ethnics and political parties supported the candidates. Native Malay candidates were failed due to the lack of contribution to the people of Malay ethnic in particular and the Riau Islands in general.